Pengaruh Ekstrak Daun Jarak (Jatropha curcas) terhadap Peradangan - Muhammad Zahran Saputra; Ardi Mustakim (Inovasi Kesehatan Global, 2026)
Inflammation is a biological response that occurs as a defense mechanism of the body against tissue damage, infection, or exposure to harmful stimuli. Excessive or prolonged inflammation can lead to various chronic diseases and negatively affect overall health. Natural compounds derived from medicinal plants have gained attention as alternative anti-inflammatory agents due to their relatively lower side effects compared to synthetic drugs. Jatropha curcas is a plant traditionally used in herbal medicine and is known to contain various bioactive compounds. This study aims to examine the effect of Jatropha curcas leaf extract on inflammatory responses. The research method used was an experimental laboratory approach with extract preparation through maceration techniques. The anti-inflammatory effect was evaluated based on changes in inflammatory indicators observed during the treatment process. The results showed that Jatropha curcas leaf extract demonstrated potential anti-inflammatory activity, which was indicated by a reduction in inflammatory signs. The presence of secondary metabolites such as flavonoids, tannins, and saponins is suspected to contribute to this effect. These findings suggest that Jatropha curcas leaf extract has promising potential as a natural anti-inflammatory agent. Further research is recommended to explore dosage optimization and toxicity levels for safe therapeutic use.